Cancer-related bone pain - editor; Andrew Davies (Oxford University Press, 2007)
Cancer patients identify bone pain as the most disruptive cancer-related event in terms of their quality of life and daily functioning, and it is also associated with increased incidence of morbidity, depression, and anxiety. Part of the Oxford Pain Management Library, this volume summarises the latest evidence-based and practical information on the management of cancer-related bone pain. Chapters cover the pathophysiology and clinical features of bone pain, general principles of management and the use of opioids and other agents. It will be an invaluable reference for all health care professionals involved in the management of patients with bone pain from various disciplines including palliative care, anaesthetics, oncology and general practice